Optimization-Based Design of a Small Pneumatic-Actuator-Driven Parallel Mechanism for a Shoulder Prosthetic Arm with Statics and Spatial Accessibility Evaluation. (8th July 2013) - Sekine, Masashi; Sugimori, Kento; Gonzalez, Jose; Yu, Wenwei
Human arms undertake most tasks in the activities of daily living (ADLs). When designing shoulder prostheses for high-level upper-limb amputees, we should consider not only how to realize high degrees of freedom under weight and shape constraints but also the user's individual task space in daily life. An appropriate mechanical structure that can make full use of state-of-the-art actuators and a scheme to optimize the structure's configuration to match users' spatial access and manipulability requirements are essential. In our previous research, a small pneumatic-actuator-driven parallel mechanism was studied as a shoulder prosthetic arm. In this paper, a systematic procedure is proposed to design the mechanism for a shoulder prosthesis considering force and spatial accessibility. This procedure includes ADL measurements to obtain the task spaces for individual subjects, indexes to evaluate the force and spatial accessibility and an optimization process based on kinematic and statics models. With this approach, the parallel mechanism was optimized for one important ADL task group, considering the trade-off between its required force and working space. Moreover, it was confirmed that the proposed design procedure could find solutions for various spatial specifications. That is, the approach could be used for individualized shoulder prosthesis design.